Design and synthesis of eugenol/isoeugenol glycoconjugates and other analogues as antifungal agents against Aspergillus fumigatus - Goswami, Lakshmi; Gupta, Lovely; Paul, Sayantan; Vermani, Maansi; Vijayaraghavan, Pooja; Bhattacharya, Asish K. (RSC Medicinal Chemistry, 2022)
Glycoconjugates are biologically significant molecules as they tend to serve a wide range of intra- and extra-cellular processes depending on their size and complexity. The secondary metabolites of the plant Myristica fragrans, eugenol and isoeugenol, have shown antifungal activities (IC50 1900 mu M). Therefore, we envisioned that glycoconjugates based on these two scaffolds could prove to be potent antifungal agents. Triazole-containing compounds have shown prominent activities as antifungal agents. Based on this, we opined that a Cu(i) catalyzed click reaction could serve as the bridging tool between a eugenol/isoeugenol moiety and sugars to synthesize eugenol/isoeugenol based glycoconjugates. In our present work, we have coupled propargylated eugenol/isoeugenol and azido sugar to furnish eugenol/isoeugenol based glycoconjugates. In another approach, we have carried out hydroxylation of the double bond of eugenol and subsequent azidation of a primary alcohol followed by intramolecular coupling reactions leading to various other analogues. All the synthesized compounds were assayed against an opportunistic pathogenic fungus, Aspergillus fumigatus. Among the synthesized compounds, two analogues have exhibited significant antifungal activities with IC50 values of 5.42 and 9.39 mu M, respectively. The study suggested that these two analogues inhibit cell wall-associated melanin hydrophobicity along with the number of conidia. The synthesized compounds were found to be non-cytotoxic to an untransformed cell line.

Design and synthesis of 1,3-diynes as potent antifungal agents against aspergillus fumigatus - Goswami, Lakshmi; Gupta, Lovely; Paul, Sayantan; Vijayaraghavan, Pooja; Bhattacharya, Asish K. (ChemMedChem, 2023)
Eugenol and isoeugenol, secondary metabolites isolated from the plant Myristica fragrans have displayed antifungal activities against Aspergillus fumigatus (IC50 1900 mu M). Compounds having conjugated unsaturation have been of great use as antifungals i. e. amphotericin B, nystatin and terbinafine etc. Hence, in the present study, we have designed and synthesised 1,3-diynes by utilizing Glaser-Hay and Cadiot-Chodkiewicz coupling reactions to furnish possible antifungal agents. Synthesis of 1,6-diphenoxyhexa-2,4-diyne derivatives was achieved by Cu(I) catalysed coupling of propargylated eugenol, isoeugenol, guaiacol, vanillin and dihydrogenated eugenol or eugenol in good to excellent yields. All the synthesized compounds were evaluated against pathogenic fungus A. fumigatus. Among all the synthesized compounds, one of the compounds was found to be exhibiting promising antifungal activity with IC50 value of 7.75 mu M thereby suggesting that this type of scaffold could pave the way for developing new antifungal agents. The most active compound was found to be low cytotoxic when assayed against L-132 cancer cell line. Effect of the most active compound on ergosterol biosynthesis has also been studied. Also, the most active compound exhibited significant anti-biofilm activity although the concentration was found to be higher than its anti-fungal activity. Morphological changes in the biofilm were remarkable under confocal laser scanning microscopy.
Keywords: 1; 3-Diynes; Antifungal agents; Aspergillus fumigatus; Cadiot-Chodkiewicz; Glaser-Hay